2016
DOI: 10.1038/srep36902
|View full text |Cite
|
Sign up to set email alerts
|

High Hepsin expression predicts poor prognosis in Gastric Cancer

Abstract: Hepsin, a membrane-associated serine protease, is frequently upregulated in epithelial cancers and involved in cancer progression. Our study aims to describe the expression pattern and evaluate the clinical implication of hepsin in gastric cancer patients. The mRNA expression of hepsin was analyzed in 50 gastric cancer and matched non-tumor tissues, which was downregulated in 78% (39/50) of gastric cancer. By searching and analyzing four independent datasets from Oncomine, we obtained the similar results. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Hepsin is another efficient cellular activator of HGF/SF . It is expressed in the liver, kidney and some other epithelial tissues (Table ) and is reported to be involved in the progression of prostatic, renal, gastric, ovarian, and breast cancers . Meanwhile, matriptase and hepsin cleave the extracellular domains of various RTKs, such as epidermal growth factor receptor (EGFR), Her2, insulin receptor, insulin‐like growth factor‐1 receptor, and PDGFR .…”
Section: Ttsps: Localized Cellular Activators Of Hgf/sf In Epithelialmentioning
confidence: 99%
“…Hepsin is another efficient cellular activator of HGF/SF . It is expressed in the liver, kidney and some other epithelial tissues (Table ) and is reported to be involved in the progression of prostatic, renal, gastric, ovarian, and breast cancers . Meanwhile, matriptase and hepsin cleave the extracellular domains of various RTKs, such as epidermal growth factor receptor (EGFR), Her2, insulin receptor, insulin‐like growth factor‐1 receptor, and PDGFR .…”
Section: Ttsps: Localized Cellular Activators Of Hgf/sf In Epithelialmentioning
confidence: 99%
“…As hepsin belongs to the transmembrane type II serine protease superfamily and has also been related with different malignant tumors [ 14 , 15 ], we performed a similar study to evaluate the interaction between hepsin and native or prelatent AT. Unlike the previous case, the results point toward native AT being capable of establishing a covalent complex with hepsin under both reducing and non-reducing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, other serine proteases could fall under the control of AT or of its different forms. One example is hepsin, which belongs to the transmembrane type II serine protease superfamily and whose expression has been related with different tumors such as prostate, cervix or gastric cancer [ 14 , 15 ]. AT inherits the structural flexibility of the serpins that enables it to carry out its inhibitory function on its target proteases [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Tanimoto et al [17], the effect of hepsin serine protease in patients with ovarian carcinoma showed that hepsin expression increased in patients with ovarian carcinoma. In a study by Zhang et al [18] on patients with gastric carcinoma, high hepsin expression was associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 97%